11-(3x-6)+2(2x+5)-x=

Simple and best practice solution for 11-(3x-6)+2(2x+5)-x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-(3x-6)+2(2x+5)-x= equation:


Simplifying
11 + -1(3x + -6) + 2(2x + 5) + -1x = 0

Reorder the terms:
11 + -1(-6 + 3x) + 2(2x + 5) + -1x = 0
11 + (-6 * -1 + 3x * -1) + 2(2x + 5) + -1x = 0
11 + (6 + -3x) + 2(2x + 5) + -1x = 0

Reorder the terms:
11 + 6 + -3x + 2(5 + 2x) + -1x = 0
11 + 6 + -3x + (5 * 2 + 2x * 2) + -1x = 0
11 + 6 + -3x + (10 + 4x) + -1x = 0

Reorder the terms:
11 + 6 + 10 + -3x + 4x + -1x = 0

Combine like terms: 11 + 6 = 17
17 + 10 + -3x + 4x + -1x = 0

Combine like terms: 17 + 10 = 27
27 + -3x + 4x + -1x = 0

Combine like terms: -3x + 4x = 1x
27 + 1x + -1x = 0

Combine like terms: 1x + -1x = 0
27 + 0 = 0
27 = 0

Solving
27 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x+14-6=7 | | 45+16-2=14 | | (3*1500)+(4*x)+(3*200)=10,500 | | 0.4m-3= -1 | | 3x-5(x-5)=-6+3+21 | | 6+12+3=39 | | 45-16+2=14 | | y=7x^2-4x-8 | | 3-18x+4=-88 | | 2-(9-a)=4a-10 | | .75*q=15 | | 14*4-6=12 | | x(2x+1)-(4x-5)= | | v^3=1944 | | -6+4n=7n+8(n+2) | | x-.35x=14.95 | | 14+5-2=12 | | .75*8=15 | | 3x+4=2(3-y) | | x-.15x=20.40 | | 3x+4=2(3-y)y | | -4(5x-3)=-3 | | 16+-4=6 | | 3x+50=7x-10 | | 16-4=3 | | 5k(3-2m)+4(3m-5k)= | | -63-15x=-8x | | 6+3r=1+4r+1 | | -9(2x-y)-(x-y)= | | 12+-5=12 | | 4,125+215x=225x+3,615.50 | | 6(2g-4h)-(3G-7h)= |

Equations solver categories